2000
DOI: 10.1890/0012-9658(2000)081[1206:tioanm]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of a Nonindigenous Marine Predator in a California Bay

Abstract: Coastal marine ecosystems worldwide are being altered rapidly by the invasion of nonindigenous species. Unlike terrestrial and freshwater systems, the impacts of an invading species have never been quantified on multiple trophic levels for a marine food web. We measured the impact of the nonindigenous green crab, Carcinus maenas, on a coastal marine food web in central California and found that this predator exerted strong ''top-down'' control, significantly reducing the abundances of several of the 20 inverte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
230
1
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 333 publications
(238 citation statements)
references
References 84 publications
5
230
1
2
Order By: Relevance
“…However, when alternate prey was present adult predation rates increased dramatically due to consumption of Hemigrapsus. Previous work by Grosholz et al (2000) found similar trends with adult Carcinus housed with a single prey crab consuming Hemigrapsus at a much higher frequency than juvenile conspecifics. Whether observed differences in predation rates are due to predator preference or differences in ease of capture between species, cannibalism rates of adult Carcinus on juveniles were very low in the presence or absence of similar alternate prey.…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…However, when alternate prey was present adult predation rates increased dramatically due to consumption of Hemigrapsus. Previous work by Grosholz et al (2000) found similar trends with adult Carcinus housed with a single prey crab consuming Hemigrapsus at a much higher frequency than juvenile conspecifics. Whether observed differences in predation rates are due to predator preference or differences in ease of capture between species, cannibalism rates of adult Carcinus on juveniles were very low in the presence or absence of similar alternate prey.…”
Section: Discussionsupporting
confidence: 73%
“…Harbor in 1993, since which time it has altered community composition and significantly reduced the abundance of some native infauna and epifauna (Grosholz et al 2000). The other locations related to this study are Tomales Bay (38°10'16.60" N 122°54'45.98" W) and Elkhorn Slough (36°49'00.61" N 121°44'49.21" W).…”
Section: Study Sitesmentioning
confidence: 94%
See 3 more Smart Citations